Cross-linguistic similarity norms for Japanese–English translation equivalents - Allen, David; Conklin, Kathy (Springer Verlag, 2013)
Formal and semantic overlap across languages plays an important role in bilingual language processing systems. In the present study, Japanese (first language; L1)–English (second language; L2) bilinguals rated 193 Japanese–English word pairs, including cognates and noncognates, in terms of phonological and semantic similarity. We show that the degree of cross-linguistic overlap varies, such that words can be more or less “cognate,” in terms of their phonological and semantic overlap. Bilinguals also translated these words in both directions (L1–L2 and L2–L1), providing a measure of translation equivalency. Notably, we reveal for the first time that Japanese–English cognates are “special,” in the sense that they are usually translated using one English term (e.g., コール /kooru/ is always translated as “call”), but the English word is translated into a greater variety of Japanese words. This difference in translation equivalency likely extends to other nonetymologically related, different-script languages in which cognates are all loanwords (e.g., Korean–English). Norming data were also collected for L1 age of acquisition, L1 concreteness, and L2 familiarity, because such information had been unavailable for the item set. Additional information on L1/L2 word frequency, L1/L2 number of senses, and L1/L2 word length and number of syllables is also provided. Finally, correlations and characteristics of the cognate and noncognate items are detailed, so as to provide a complete overview of the lexical and semantic characteristics of the stimuli. This creates a comprehensive bilingual data set for these different-script languages and should be of use in bilingual word recognition and spoken language research.